Extreme precipitation on the Island of Madeira on 20 February 2010 as seen by satellite passive microwave sounders - Levizzani, Vincenzo (2013)
Extreme rainfall on the Island of Madeira on 20 February 2010 triggered flash floods and mudslides with 45 casualties, 8 missing people, and 100 injured. The NE-moving frontal system originating from a low-pressure center in the Madeira Archipelago is not unusual for the area, but its consequences on the island were rather extreme. The study dwells on passive microwave sounders from polar orbiters for the retrieval of rainfall intensity and cloud classification. Heavy rainfall was generated by severe local convection and enhanced over the central mountain chain. Physical cloud classification identifies the shallow convective precipitation type lasting for a few hours around noon and the observations confirm the numerical model results.